Cognitive potency and safety of tDCS treatment for major depressive disorder: a systematic review and meta-analysis - Wang, Junjie; Yao, Xinru; Ji, Yuqi; Li, Hong (Frontiers in Human Neuroscience, 2024)
Background. The benefits of transcranial direct current stimulation (tDCS) for patients with major depression disorders are well established, however, there is a notable research gap concerning its comprehensive effects on both depressive symptoms and cognitive functions. Existing research is inconclusive regarding the cognitive enhancement effects of tDCS specifically in MDD patients. The present study aims to fill this knowledge gap by scrutinizing the most updated evidence on the effectiveness of tDCS in anti-depressive treatment and its influence on cognitive function.A systematic review was performed from the first date available in PubMed, EMBASE, Cochrane Library, and additional sources published in English from 1 January 2001 to 31 May 2023. We examined cognitive outcomes from randomised, sham-controlled trials of tDCS treatment for major depression. The evaluation process strictly followed the Cochrane bias risk assessment tool into the literature, and meta-analysis was performed according to the Cochrane System Reviewer's Manual.Results. In this quantitative synthesis, we incorporated data from a total of 371 patients across 12 studies. Results showed significant benefits following active tDCS compared to sham for the antidepressant effect (SMD: -0.77 [-1.44, -0.11]).Furthermore, active relative to sham tDCS treatment was associated with increased performance gains on a measure of verbal memory (SMD: 0.30 [-0.02, 0.62]). These results did not indicate any cognitive enhancement after active tDCS relative to sham for global cognitive function, whereas there was a noticeable trend towards statistical significance specifically in the effect of verbal memory.Our study offers crucial evidence-based medical support for tDCS in antidepressant and dimension-specific cognitive benefits. Further well-designed, large-scale randomized sham-controlled trials are warranted to further validate these findings.